Uji Efektivitas Ekstrak Buah Andaliman (Zanthoxylum acanthopodium. D.C) Terhadap Phytophthora palmivora Penyebab Penyakit Busuk Buah Kakao (Theobroma cacao L.) - GINTING, BERTA BR; SUPRAPTA, DEWA NGURAH; SUNITI, NI WAYAN (Agrotrop : Journal on Agriculture Science; Vol 12 No 1 (2022), 2022)
Effectiveness Test of Andaliman Fruit Extract ( Zanthoxylum acanthopodium . D.C) Against Phytophthora palmivora the Cause of Cocoa ( Theobroma cacao L.) pod rot disease. Fruit rot disease caused by the fungus Phytophthora palmivora causes the loss of crop yields up to 90%. Therefore, an effort is needed to control Phytophthora palmivora that causes blight in cocoa plantations. Alternative that can be done is the use of botanical fungicides. One of the plants that can be used as a botanical fungicide is the fruit of Andaliman ( Zanthoxylum acanthopodium D.C). This study aims to test the effectiveness of andaliman fruit extract against P. palmivora which causes pod rot disease. Colony test and cocoa pod damage test in vivo using extract concentrations, namely 50%; 25%; 16.7%; and 0% (control). The results showed that andaliman fruit extract could inhibit the growth of P. palmivora which can be used as botanical fungicide. The concentration of andaliman fruit extract 50% and 25% can reduce cocoa pod damage caused by P. palmivora by 58% and 45.7%, respectively.